Nano-Dispersed Ziegler-Natta Catalysts for 1 μm-Sized Ultra-High Molecular Weight Polyethylene Particles - Chammingkwan, Patchanee; Bando, Yusuke; Terano, Minoru; Taniike, Toshiaki (Frontiers in Chemistry, 2018)
A catalytic approach to synthesize microfine ultra-high molecular weight polyethylene (UHMWPE) particles was proposed based on the exploitation of nano-sized catalysts. By utilizing MgO nanoparticles as a core material, a Ziegler-Natta-type MgO/MgCl2/TiCl4 core-shell catalyst with the particle size in a nano-range scale was prepared in a simple preparation step. The organic modification of MgO surfaces prior to catalyzation prevented agglomeration and facilitated the full dispersion of catalyst particles at a primary particle level for the first time. The nano-dispersed catalysts successfully afforded a direct access to UHMWPE having the particle size in the range of 1-2 m at a reasonable activity. Extremely fine polymer particles yielded several advantages, especially at a significantly lower fusion temperature in compression molding.